Minding the gap-relating disclosure to contexts of sustainability reporting in the automotive industry - Imke Rhoden; Christopher Stephen Ball; Stefan Vögele; Wilhelm Kuckshinrichs (Corporate Social Responsibility and Environmental Management, 2022)
Sustainability is a major issue in the automotive sector and players are at different points in their transition. Adopting a multi-method approach, we identify the positioning of automotive manufacturers in relation to sustainability, highlighting the main foci of their sustainability strategies. This is achieved using a topic model based on automated language processing. Subsequently, we use a Seemingly Unrelated Regression model, applied to manufacturers' operational data, to establish the degree of alignment between sustainability strategies and operations. Results show that sustainability in the automotive sector is highly differentiated and manufacturers emphasize diverging topics in their communication strategy and have different production practices. In relation to sustainability reporting, we identify certain operational variables, which are significantly related with certain dominant sustainability narratives.
Keywords: 650; automotive industry; corporate social responsibility; seemingly unrelated regression; sustainability reporting; text analysis